Growth and mineral nutrition of sida rhombifolia Crescimento e nutrição mineral de sida rhombifolia - Bianco S. (2014)
This experiment was carried out to analyze dry mass production and distribution, and the content and accumulation of macronutrients in arrowleaf sida (Sida rhombifolia) plants cultivated under mineral nutrition standard conditions. Plants grew in seven liter pots filled with sand substrate and daily irrigated with nutrient solution, under greenhouse conditions. Treatments consisted of times of evaluation (21, 35, 49, 63, 77, 91, 105, 119, and 133 days after emergence - DAE) and were arranged in a completely randomized design with four replicates. Arrowleaf sida plants showed small accumulation of dry mass (0.3 g per plant) and macronutrients (6.9 mg N per plant, 0.7 mg P per plant, 8.6 mg K per plant, 4.9 mg Ca per plant, 2,6 mg Mg per plant, and 0.3 mg S per plant) at the vegetative growth stage (< 49 DAE). Those accumulations increased, mainly after 63 DAE, and the daily accumulation rate was crescent up to 94 DAE (dry mass - DM), 89 DAE (N and P), 98 DAE (K), 95 DAE (Ca and S), and 93 DAE (Mg), when there was accumulation of 26.3 g DM per plant, 402.6 mg N per plant, 45.6 mg P per plant, 359.3 mg K per plant, 337.6 mg Ca per plant, 71.9 mg Mg per plant, and 20.9 mg S per plant. N and K had the highest rates and, consequently, were the most required and accumulated in greater amounts in plant tissues of arrowleaf sida.